Outbreak of human astroviruses 1 and Melbourne 2 in acute gastroenteritis pediatric patients in Japan during the COVID-19 pandemic, 2021 - Hiroshi Ushijima; Shuichi Nishimura; Yuko Shimizu-Onda; Ngan Thi Kim Pham; Quang Duy Trinh; Shoko Okitsu; Chika Takano; Kattareeya Kumthip; Sheikh Ariful Hoque; Shihoko Komine-Aizawa; Niwat Maneekarn; Satoshi Hayakawa; et al. (Elsevier, 2023)
Background: Human astrovirus (HAstV) infection is one of the leading causes of acute gastroenteritis in young children. The present study reports the outbreak of HAstV in children with acute gastroenteritis in Kyoto, Japan, during the COVID-19 pandemic, 2021. Methods: A total of 61 stool samples were collected from children with acute gastroenteritis who visited a pediatric outpatient clinic in Maizuru city, Kyoto, Japan from July to October, 2021. HAstV was screened by RT-PCR, and the genotypes were identified by nucleotide sequence analysis. Results: Of 61 cases of acute gastroenteritis, 20 were mono-infected with HAstV alone. In addition, mixed infection of HAstV and NoV, and HAstV and RVA were also detected in 15 and 1 cases, respectively. Of 36 HAstV strains detected in this outbreak, 29 and 7 were HAstV1 and MLB2 genotypes, respectively. All HAstV1 strains were closely related to the HAstV1 reported from Thailand and Japan in 2021 and all of them belonged to subgenotype HAstV1a. Among MLB2, they were most closely related to the MLB2 strains reported from China in 2016 and 2018. Conclusions: After the kindergartens and schools were re-opened at the middle of 2021 in Japan, an outbreak of HAstV was reported. Control measures against the COVID-19 pandemics might affect the spread of diarrheal virus infection. Here we report the outbreak of HAstV1 and MLB2 in Kyoto, Japan, during COVID-19 pandemic in 2021.